2007
DOI: 10.1038/sj.cdd.4402263
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the prosurvival activity of nerve growth factor on cardiac myocytes

Abstract: Neurotrophins (NTs) control neuron survival and regeneration. Recent research showed that NTs possess cardiovascular actions. In this study, we investigated the hypothesis that the NT nerve growth factor (NGF) prevents cardiomyocyte apoptosis. We demonstrated that cultured rat neonatal cardiomyocytes (RNCMs) produce NGF and express its trkA (tropomyosin-related receptor A (NGF high-affinity receptor)) receptor. RNCMs given a neutralizing antibody for NGF or the trkA inhibitor K252a underwent apoptosis, thus su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
101
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 36 publications
(61 reference statements)
7
101
1
Order By: Relevance
“…In general, an increase of NGF expression can be observed both in atria and ventricles. Since NGF also exerts anti-apoptotic effects via its main receptor TrkA (Caporali et al 2008), the observed NGF increase may in fact represent a reflex mechanism to an increased degree of apoptosis in aging myocardium. Since apoptosis and fibrosis in the atria and even in healthy hearts seem to develop with age (Olivetti et al 1997;Centurione et al 2002), the continuous increase of NGF may be in line with such a hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, an increase of NGF expression can be observed both in atria and ventricles. Since NGF also exerts anti-apoptotic effects via its main receptor TrkA (Caporali et al 2008), the observed NGF increase may in fact represent a reflex mechanism to an increased degree of apoptosis in aging myocardium. Since apoptosis and fibrosis in the atria and even in healthy hearts seem to develop with age (Olivetti et al 1997;Centurione et al 2002), the continuous increase of NGF may be in line with such a hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, NGF has been identified as a pro-survival factor for cardiomyocytes by developing anti-apoptotic effects via tyrosine kinase A (TrkA) receptor downstream signaling (Caporali et al 2008). With regard to its pivotal role in the integrity of cellular and subcellular systems, the autonomic nervous system has been further shown to be involved in heart rate, rhythm, and contractility (Wasmund et al 2003;Meyer et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, NGF has been shown to be present in neonatal rat myocytes, where it acts as an autocrine survival factor. In addition, increasing the expression of NGF protected the cells from ANG II-induced apoptosis, and, in a rat model of myocardial infarction, NGF gene transfer promoted cardiomyocyte survival (10). Similarly, BDNF gene deletion severely affects heart development, leading to premature death in mice (14,16), and mice lacking the receptor for BDNF (TrkB) die immediately after birth (1).…”
mentioning
confidence: 99%
“…The interaction between NGF and its receptor in cardiomyocytes causes a prosurvival signal of transcriptional factors [31]. For several cardiac diseases (MI, CAD) Rana and colleagues reported that cellular stretch leads to a decrease of NGF mRNA and protein expression in cardiomyocytes [32].…”
Section: Discussionmentioning
confidence: 99%